ORGANIZATIONAL BEHAVIOR AND LABOR PRODUCTIVITY IN A COMPANY GASTRONOMIC (LACCEI, 2024)
At present, all companies consider the importance of human resources, because these are who will carry out the activities of the companies thus fulfilling its stated objectives and goals. In addition, human resources are those who participate in productivity of every company, in these times of enormous changes, the companies seek information and methods for improvement constant, which will allow the company to be more competitive, and efficiently use its resources. In order to determine the relationship one of the strategies that affects productivity, the proposed objective: to determine the relationship between the behavior organization and productivity. as well as find the relationship of organizational behavior and motivation, job satisfaction, staff competence and training and personal development. The sample consisted of 15 collaborators, provided them with 2 previously validated instruments statistically and by expert judgment. It was proposed as a type research, to the descriptive correlational cut cross. The results that were reached were that, yes there is a relationship between organizational behavior and labor productivity, according to the Spearman coefficient = .840**. It was also found that behavior organization is perfectly related to motivation and job satisfaction (r=1), the results showed that the relationship between organizational behavior and competence of the personnel have a relationship of .792**. finally confirmed that there is no relationship between organizational behavior and training and staff development. (r=-.103). it is concluded that the behavior in the organization is closely related to employee productivity.